Immunohistochemical Expression of Nuclear β-Catenin and STAT-6 in a Solitary Fibrous Tumor of the Soft Palate: A Case Report and Review of the Literature - Ivonne A. Montes-Mojarro; Javier Baquera-Heredia; Juan Felipe Sanchez-Marle; Carlos Ortiz-Hidalgo (Iranian Society of Pathology, 2017)
The solitary fibrous tumors (SFT) are rare tumors in the head and neck region and there have been only 5 cases reported in the literature in the soft palate. The current paper presents a unique case of a 62-year-old male with TFS arising in the soft palate. The tumor was highly cellular, composed of bland looking haphazardly arranged spindle cells. The signal transducer and activator of transcription (STAT)-6 and nuclear β-catenin were reactive by immunohistochemistry (IHC). The current case highlights the importance of the STAT-6 and the β-catenin as IHC markers to make a differential diagnosis with other entities. In summary, the paper presents the first reported case of a SFT of the soft palate in a male patient with nuclear expression of STAT-6 and β-catenin.